Problems and Guidelines of Problems Solving on the Community Relationship of School under the Office of Uttaradit Primary Educational Service Area Office 1-2 - Klinkhajorn, Jariyaporn; Rattanarasri, Kitti (Ratchaphruek Journal, 2021)
This research aimed to study the problems and how to solve the problem of community relationships of schools under the Office of Uttaradit Primary Educational Service Area 1-2, Uttaradit Province. Sample of study were 109 the school director and 108 school teachers under the Office of Uttaradit Primary Educational Service Area, Academic year 2018, the total of 217 people. The research tool was questionnaire. Data were analyzed by using frequency (F), percentage (%), mean ( ), and standard deviation (S.D.). The study results were found that: 1. Community relationship problems of schools under the Office of Uttaradit Primary Education Service Area 1-2 Uttaradit Province mostly found in low level ( = 2.69). the most problem was community service ( = 2.66), the second was receiving assistance and support from the community ( = 2.67), and third side was strengthening the relationship with the community ( = 2.75). 2. Guidelines of solving the problems for community relationship with schools under the Office 1-2 of Uttaradit Primary were that the schools need fund on materials and equipment to support students’ learning and community services. Moreover, schools and community have to make the co-operative survey for learning center, and arrange the meeting for the school committee to have an opportunity in school management.